The Fashion Semiotics of 2024 Indonesian President and Vice President Candidates in Mass Media - Erica Rachel Budianto (Institute of Research and Community Outreach - Petra Christian University, 2026)
Fashion can function as a political communication tool by shaping public perceptions of political figures through mass media. This study systematically investigates the fashion semiotics of all presidential and vice-presidential candidates featured in Indonesian mass media during the 2024 Indonesian Presidential Election campaign. It aims to examine how clothing choices communicate implicit meanings and function as visual strategies for constructing political identities, populist images, and connections with voters. Employing a qualitative research approach, the study explores the diversity of fashion representations and interprets their meanings through descriptive analysis. Roland Barthes’ semiotic theory and a visual culture framework are applied to analyze the denotative, connotative, and ideological meanings embedded in candidates’ clothing, including styles, colors, and visual appearances. The study focuses comparatively on all three presidential and vice presidential candidate pairs to identify similarities and differences in their use of fashion as political communication. Its novelty lies in moving beyond previous candidate-specific studies by providing a comparative semiotic analysis of fashion across all competing candidate pairs in the 2024 election. The study contributes to study on fashion, semiotics, visual culture, and political communication by demonstrating how clothing operates as a strategic visual resource in contemporary populist electoral discourse.